An improved, scalable synthesis of Notum inhibitor LP-922056 using 1-chloro-1,2-benziodoxol-3-one as a superior electrophilic chlorinating agent - Willis, Nicky J.; Bayle, Elliott D.; Papageorgiou, George; Steadman, David; Atkinson, Benjamin N.; Mahy, William; Fish, Paul V. (Beilstein Journal of Organic Chemistry, 2019)
Background: The carboxylesterase Notum has been shown to act as a key negative regulator of the Wnt signalling pathway by mediating the depalmitoleoylation of Wnt proteins. LP-922056 (1) is an orally active inhibitor of Notum. We are investigating the role of Notum in modulating Wnt signalling in the central nervous system and wished to establish if 1 would serve as a peripherally restricted control. An accessible and improved synthetic route would allow 1 to become more readily available as a chemical tool to explore the fundamental biology of Notum and build target validation to underpin new drug discovery programs.Results: An improved, scalable synthesis of 1 is reported. Key modifications include: (1) the introduction of the C7-cyclopropyl group was most effectively achieved with a Suzuki–Miyaura cross-coupling reaction with MIDA-boronate 11 (5 → 6), and (2) C6 chlorination was performed with 1-chloro-1,2-benziodoxol-3-one (12) (6 → 7) as a mild and selective electrophilic chlorination agent. This 7-step route from 16 has been reliably performed on large scale to produce multigram quantities of 1 in good efficiency and high purity. Pharmacokinetic studies in mouse showed CNS penetration of 1 is very low with a brain/plasma concentration ratio of just 0.01. A small library of amides 17 were prepared from acid 1 to explore if 1 could be modified to deliver a CNS penetrant tool by capping off the acid as an amide. Although significant Notum inhibition activity could be achieved, none of these amides demonstrated the required combination of metabolic stability along with cell permeability without evidence of P-gp mediated efflux.Conclusion: Mouse pharmacokinetic studies demonstrate that 1 is unsuitable for use in models of disease where brain penetration is an essential requirement of the compound but would be an ideal peripherally restricted control. These data will contribute to the understanding of drug levels of 1 to overlay with appropriate in vivo efficacy endpoints, i.e., the PK-PD relationship. The identification of a suitable analogue of 1 (or 17) which combines Notum inhibition with CNS penetration would be a valuable chemical probe for investigating the role of Notum in disease models.
Keywords: brain penetration; 1-chloro-1,2-benziodoxol-3-one; electrophilic chlorination; LP-922056; Notum inhibitor